2019
DOI: 10.15283/ijsc18096
|View full text |Cite
|
Sign up to set email alerts
|

Toward a Reconceptualization of Stem Cells from Cellular Plasticity

Abstract: The slow progress in clinical applications of stem cells and the bewildering mechanisms involved have puzzled many researchers. Recently, the increasing evidences have indicated that cells have superior plasticity in vivo or in vitro, spontaneously or under extrinsic specific inducers. The concept of stem cells may be challenged, or even replaced by the concept of cell plasticity when cell reprogramming technology is progressing rapidly. The characteristics of stem cells are manifestations of cellular plastici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 56 publications
0
1
0
Order By: Relevance
“…Of note, although the transdifferentiation concept is still controversial, especially for in vitro studies, recent studies have demonstrated that adult cell transition can occur spontaneously in vivo under physiological or pathological conditions [44][45][46]. However, evidence of this mechanism in the physiology of age-related bone loss has not yet been proven in vivo.…”
Section: Plos Onementioning
confidence: 99%
“…Of note, although the transdifferentiation concept is still controversial, especially for in vitro studies, recent studies have demonstrated that adult cell transition can occur spontaneously in vivo under physiological or pathological conditions [44][45][46]. However, evidence of this mechanism in the physiology of age-related bone loss has not yet been proven in vivo.…”
Section: Plos Onementioning
confidence: 99%